Studi tentang Pandangan Anggota Jemaat GBKP Kuta Buluh mengenai Tuhan, Gereja Petani dan Kerja Sebagai Petani - Eder Timanta Sitepu; Ebenhaizer Imanuel Nuban Timo (Cipanas Theological Seminary, 2023)
Agriculture is considered a sector of work that does not humanize humans. This happens because the farmer profession does not provide results that are in accordance with the risks of the work done. In addition, the church as one of the organizations that lives in the context of agriculture still revolves around worship rituals. The Church has not responded well to the agricultural context. This has led to a decrease in congregation members' appreciation of God's presence in the context of agriculture. It also causes the work as a farmer not to be considered a gift from God, but a job that is not worth doing. This paper aims to see the views of Batak Karo Protestant Church (GBKP) Kuta Buluh congregation members regarding God, the farmer's church and work as a farmer. The results show that members of GBKP Kuta Buluh Church still feel God's presence in their lives as farmers. Members of GBKP Kuta Buluh congregation argue that life as a farmer is God's gift. However, there are also members of the GBKP Kuta Buluh congregation who consider that the farmer profession is an unworthy job. In addition, the church is considered to have not responded well to agricultural life, so the church has not had a positive impact on the lives of members of the congregation who live in the context of agriculture.